PTU-205 The significance of elevated neutrophil: lymphocyte ratios in patients receiving chemoradiotherapy treatment for squamous cell carcinoma of the anus. (22nd June 2015) - Bulla, R; Humes, D; Scholefield, J; Walter, CJ
Abstract : Introduction: A recently published single-centre, retrospective study examined neutrophil:lymphocyte ratios (NLRs) in patients with squamous cell carcinoma of the anus and found a strong association with prognosis. 1 This study aimed to examine if the previously reported relationship between pretreatment NLRs and survival in patients undergoing chemoradiotherapy treatment of squamous cell carcinoma of the anus was also seen at our centre. Method: All patients diagnosed with squamous cell carcinoma of the anus between 2005–2012 at Nottingham University Hospitals NHS Trust (NUH) were identified from the multidisciplinary team database. Retrospective data collection was undertaken using the electronic and case note records of those patients whose primary treatment was with chemoradiotherapy. The patients were divided into 2 groups: the non-elevated NLR group (NLR ≤5) and the elevated NLR group (NLR >5). Their baseline demographics and mortality were compared. Results: Seventy-six patients (50 female and 26 male) with a median age of 63 years (IQR 52–74) were treated at NUH for squamous cell carcinoma of the anus with chemoradiotherapy over the 8-year study period. Of these 15 (20%) demonstrated an elevated NLR at presentation. There was no significant difference in baseline demographics and follow-up times between the non-elevated and elevated NLR groups with median clinical follow-up of 36 months (IQR 24–52) and 38 months (IQR 12–44) (p = 0.4) respectively. On univariate analysis the elevated NLR group was associated with worse survival with a hazard ratio (HR) for mortality of 2.73 (95% CI 1.07–6.96). Multivariate analysis of mortality adjusting for the known confounders of age, sex and stage of disease demonstrated a HR 6.21 (95% CI 1.98–19.47). Conclusion: In this study a fifth of patients with squamous cell carcinoma of the anus demonstrated elevated NLRs at presentation. Elevated NLRs at presentation were associated with increased mortality. This association strengthened when adjusting for stage of disease at presentation. Disclosure of interest: None Declared. Reference: Toh E, Wilson J, Sebag-Montefiore D, Botterill I. Neutrophil:lymphocyte ratio as a simple and novel biomarker for prediction of locoregional recurrence after chemoradiotherapy for squamous cell carcinoma of the anus. Colorectal Dis. 2014;16(3):90–7